PROCESS AND SYSTEMS Process of care and activity in a clinically inclusive ambulatory emergency care unit: progressive effect over time on clinical outcomes and acute medical admissions. Issue 3 (2020) - Reschen, Michael E; Bowen, Jordan; Singh, Sudhir; Rajwani, Mridula; Giles, Matthew; Price, James; Lasserson, Daniel; O'Callaghan, Christopher A
No abstract available